Impact of Midwife-Led Psychoeducation on Primigravida Mothers’ Knowledge of Childbirth Fear and Childbirth Efficiency: A Review - Ann Maria Thomas, Cheeramattam; Solomon, Smriti G. (Innovational: Journal of Nursing and Healthcare, 2024)
Childbirth, often known as labor and delivery, is the procedure that ends a pregnancy and takes place when one or more infants are delivered vaginally or through cesarean section from the mother’s body. Primigravidae experience several physical and emotional changes, which can make them nervous about the birthing process. The pathological fear of pregnancy known as “childbirth fear” is one factor that can contribute to a woman delaying her delivery. It has been found that a woman’s level of childbirth self-efficacy, which is also referred to as labor and delivery confidence, is a crucial indicator of how well she will be able to cope with the physical and emotional challenges that come with giving birth. Prenatal education, prenatal counseling, prenatal training, and role-playing are all examples of psychoeducational intervention techniques that have been shown to have a significant impact on a variety of psychological outcomes, including attitudes toward childbirth, fears associated with childbirth, depression, fear, and anxiety. Their expectations for the birth procedure were elevated as a result of solutionfocused counseling, midwife-supported psychotherapy, and a midwife-led integrated pre-birth training program.